Taxonomic Study on Hill Stream Fishes - Khatri, Dambar Singh (Pragnya Sarathi प्रज्ञा-सारथि, 2025)
Hill stream fishes are the cold water fishes found in the large river of Nepal. They are distributed from upper riches of river to lower plane area where river flow with less velocity and finally meets ocean. Taxonomy is crucial for understanding species diversity, conservation efforts, and the possible impacts of global warming and habitat destruction. Taxonomy serves as a beacon of knowledge, guiding toward a deeper understanding of fish habitat in the natural world and responsibility of protection. Unraveling the relationships built out via taxonomic efforts also provides clues to issues regarding lost species, and reasons surrounding their extinction. The current study was focused on Mahakali River, its tributaries, irrigation canal and Ghols. The collected fishes were preserved in 10% formalin and photograph had been taken before preservation. On the basis of colour pattern, mouth structure, no of barbels, eyes diameter, snout structure, body length, shape of body, fin rays, lateral line scales, suckers present on ventral side, enlisted nineteen hill stream fish species by applying morphometric and meristic method.